Optimal institutions under persistent tax uncertainty - Victor Peirone (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
Various economic models ignore the complexity of green field investment and do not assign a fundamental role to institutional uncertainty on the decision making of capital expenditures. These assumptions can be applicable to developed nations, but do not certainly fit into emerging economies. We found that countries with greater volatility in taxation invest less on average. In the Argentine case, this country is among the 1/8 highest tax volatility and lowest investment economies in a sample of ninety nations. Here we explore a tool kit to analyze policies and institutional arrangements to improve pareto optimal outcome.
Keywords: 330